Behaviour Analysis of Strengthened-RC Beam with Natural Fiber Reinforced Polymer (NFRP) based on Abaca Fiber by Using Finite Element Method - Saidi, Taufiq; Hasan, Muttaqin; Amalia*, Zahra; Iqbal, Muhammad (Aceh International Journal of Science and Technology, 2022)
Synthetic fiber reinforced polymer (FRP) as an alternative composite material has been widely used for strengthening and repairing reinforced concrete structures. However, applying synthetic FRP materials is expensive and may be unsafe for the environment. Therefore, natural fiber reinforced polymer (NFRP) is the best alternative FRP, especially in increasing the shear strength of reinforced concrete beams. It has good tensile strength and also is environmentally friendly. Technological developments in the field of computing make modeling various aspects easier. One of them is modeling reinforced concrete (RC) beams. In this study, the ATENA V534 software was used to evaluate the results of the research and testing behavior of reinforced concrete beams. Behavior is evaluated in the form of load and deflection, the pattern of cracks and failure, and stress and strain of reinforcements. The numerical results obtained in ATENA V534 showed good agreement with experimental results. The maximum load of the four beams, namely BN, BSTV1, BSTV2, and BSTD1, based on the finite element method analysis results using ATENA V534 are 25,89 tons, 27,53 tons, 28,14 tons, and 26,92 tons, respectively. In contrast, the maximum load obtained from experimental results are 26,79 tons, 29,40 tons, 29,45 tons, and 27,14, respectively. The difference in crack angle in the beam between ATENA V534 and the experimental result is around 2. The results of numerical analysis using ATENA V534 show a lower maximum load value, higher stiffness, and lower deflection at maximum load compared to experimental results on all reinforced concrete beams analyzed in this study.